2014
DOI: 10.1016/j.sandf.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cation exchange capacity of soil on stabilized soil strength

Abstract: While a certain correlation between the cation exchange capacity (CEC) of the soil and the strength of the cement stabilized soil has been reported, the mechanism remains unclear. In this research, a set of soil samples with different CECs were stabilized with different proportions of cement and calcium hydroxide (Ca(OH) 2 , CH). The influence of soil CEC on the strength of the stabilized soil was investigated by analyzing the CH saturation in the pore solution and measuring the strength of the stabilized soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Similarly, Towhata et al [19] and Villar and Lloret [20] investigated temperature effects on clayey soils and showed that the changes in viscosity of water with temperature have the most important mechanism in the change of soils properties. The strength of clay soil can be affected by its cation exchange capacity, CEC [21]. Goodman et al [22] reported that beyond temperature of 100 °C, the CEC of buckshot clay soil decreased considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Towhata et al [19] and Villar and Lloret [20] investigated temperature effects on clayey soils and showed that the changes in viscosity of water with temperature have the most important mechanism in the change of soils properties. The strength of clay soil can be affected by its cation exchange capacity, CEC [21]. Goodman et al [22] reported that beyond temperature of 100 °C, the CEC of buckshot clay soil decreased considerably.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the highest Ca(OH)2 SI was −0.8, while under the sam cement addition conditions, Yu et al [25] detected supersaturated Ca(OH)2 in cemen stabilized soils with low cation exchange capacities (≤ 32 meq/100 g), which had a highe strength than those with undersaturated Ca(OH)2 and high cation exchange capacitie Hence, the authors suggest that the cation exchange process of the soil minerals was pr marily ascribed to the undersaturation of Ca(OH)2 and the slow strength increase in th cement-stabilized soils. In addition, the saturation level of CaOH + was investigated wit respect to the thermodynamic equation CaOH + →Ca 2+ +OH − , with SI values that fluctuate between 0.306 and 0.439 and a development pattern that was identical to that of Ca(OH) This result suggested that the aqueous species of Ca, which should have crystallized t Ca(OH)2, participated in the subsequent reactions in the form of CaOH + .…”
Section: The Correlation Analysis Of the Saturation Levels Between Ca...mentioning
confidence: 91%
“…Though the thermodynamic method has been successfully applied to cementitious materials, it has not been systematically extrapolated to cement-stabilized soils. Some pioneer works have calculated the SI values the minerals ettringite (AFt) [6] and Ca(OH) 2 [25] with respect to different chemically stabilized soils, which has revealed the impacts of these two minerals on the engineering performances of the respective systems. However, the influence of the coexistence of complex aqueous species on SI calculations has not been considered in previous works and the evaluation of the general chemical processes of cement-stabilized soils using a single phase may not be accurate enough since some hydrated phases (such as Ca(OH) 2 ) are the reactants of the simultaneous pozzolanic reactions of soil minerals [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Those provide an alternative to bases constructed following the deep-cold recycling technology Iwański and Chomicz-Kowalska [1], and also Iwański et al [2]. In the first place, road binders are applied to the subgrade to improve its bearing capacity and alter the bearing capacity class Iwański and Buczyński [3] oraz Yu et al [4] and Ahmed et al [5] or Chai and Miura [6]. The application range of road binders can be extended to include sub-bases, road bases, in the latter those have the form of hydraulically bound aggregate mixes WT-5 [7], and also bases treated with foamed bitumen and bitumen emulsion Iwański et al [2], also Iwański and Chomicz-Kowalska [8].…”
Section: Introductionmentioning
confidence: 99%